The Influence of Creative Work, Interpersonal Communication, and Team Cohesiveness on Team Performance in Culinary UMKM in Cirebon City - Tsany Qania Labiba; Tia Afriyani; Edy Hartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research is conducted to explore the interaction between creative work, interpersonal communication, and team cohesiveness on team performance in micro, small, and medium enterprises (MSMEs) in the culinary field in Cirebon City. This research employs a quantitative methodology through the use of surveys, involving 75 respondents who are actively involved in culinary MSMEs. Data for this research were obtained using structured questionnaires and subsequently analyzed with multiple linear regression to determine the magnitude of the influence between the independent and dependent variables. The findings indicate that creative work positively and significantly affects team performance. Similarly, interpersonal communication also exerts a significant positive influence, signifying the importance of effective message exchange and mutual understanding among team members. In addition, team cohesiveness also made a strong contribution to performance improvement through collaboration, trust, and shared goals. The results of the simultaneous test indicate that the three variables collectively have a significant impact on enhancing team performance. This research contributes to the literature of human resource management and organizational behavior, especially in the MSME sector, by emphasizing the importance of non-technical factors in supporting teamwork results. This study recommends that MSMEs invest more in building team creativity, improving communication skills, and strengthening group unity. Future research is recommended to explore other psychosocial and contextual factors that influence team performance across different types of MSMEs.